A Review of Thermal Detectors of THz Radiation Operated at Room Temperature - Zbigniew Bielecki; Janusz Mikolajczyk; Jacek Wojtas (Sensors)
This article concerns optical detection issues in the terahertz (THz) range. This is a kind of guide to various types of uncooled thermal detectors in the most often applications. Particular attention is paid to the principle of their operation, technology, and practical features. In addition, some detection methods were also characterized by comparing their performances. The article ends with a performance summary of the selected THz thermal detectors.